Enseigner la science-fiction - James Gunn (ReS Futurae)
The article delves into the complexities of teaching science fiction in academic settings. The authors notes that many sf courses focus on these themes rather than the genre itself, partly because of difficulties in gaining departmental approval and some educators’ lack of confidence in teaching sf as a distinct genre. Gunn advocates for a comprehensive survey of sf courses in high schools and colleges to better understand their prevalence and content. Drawing from his extensive teaching experience at the University of Kansas, the author describes various approaches to sf education, such as the “great books” method, the “ideas in sf” approach, and the historical perspective.